2020
DOI: 10.1111/imj.14926
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of awake prone position in hypoxaemic patients with COVID‐19: case reports and literature review

Abstract: We hereby present two case reports of moderate coronavirus disease patients, suffering from profound hypoxaemia, further deteriorating later on. A schedule pre‐planned awake prone position manoeuvres were executed during their hospital stay. Following this, the patients' saturation improved, later to be weaned from oxygen support. Paucity of evidence and data regarding this topic led us to review the concept of awake prone position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 10 publications
(13 reference statements)
0
17
0
1
Order By: Relevance
“…This case report illustrates two important findings: after survival from a severe life-threatening COVID-19 infection complicated by ARDS and multiple organ failure, our patient became sustained hypertensive throughout the convalescent period; prone positioning contributed to significant improvement of his arterial oxygenation, and the need for supplemental oxygen was substantially reduced due to less mismatch between ventilation and circulation [ 7 - 8 ].…”
Section: Discussionmentioning
confidence: 94%
“…This case report illustrates two important findings: after survival from a severe life-threatening COVID-19 infection complicated by ARDS and multiple organ failure, our patient became sustained hypertensive throughout the convalescent period; prone positioning contributed to significant improvement of his arterial oxygenation, and the need for supplemental oxygen was substantially reduced due to less mismatch between ventilation and circulation [ 7 - 8 ].…”
Section: Discussionmentioning
confidence: 94%
“…Revisão de literatura usando bases de dados, buscador genérico de internet e financiadores de saúde. Cohen, D. et al, 2020 Beneficial effect of awake prone position in hypoxaemic patients with COVID-19: case reports and literature review Revisar o conceito de posição de prona acordada após apresentar dois relatos de caso de pacientes com COVID-19 moderada.…”
Section: Resultsunclassified
“…Prone positioning in mechanically ventilated patients with COVID-19 improves oxygenation and is associated with reduced mortality [33]. Although APP similarly improves oxygenation in non-intubated patients with COVID-19 [3,[16][17][18][19][20][21][22][23], reports have failed to show bene ts on patient-centered outcomes [25,26]. A multicenter observational study, investigating a cohort of 199 patients with COVID-19 found no difference in intubation rates in patients with duration of APP for more than 16 hours per day compared with shorter duration of APP [25].…”
Section: Discussionmentioning
confidence: 99%
“…It increases lung volume [10,11], improves ventilation-perfusion ratio [12][13][14], and distributes pleural pressure more evenly [15]. Several studies report transient improvement in oxygenation during APP in a majority of patients with hypoxemic respiratory failure due to COVID-19 pneumonia [3,[16][17][18][19][20][21][22][23]. However, translating physiological improvement into clinically relevant outcomes has not been supported by ARDS-studies [24] and there remains a gap in the current knowledge for the use of APP [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%